PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN, AUDIT TENURE, DAN REPUTASI KAP TERHADAP OPINI AUDIT GOING CONCERN - Tandungan, Debby; Mertha, I Made (E-Jurnal Akuntansi, 2016)
Going concern issues are complex so that need factors that used as a benchmark in determining the company’s going concern status. This study aimed to examine the effect of the audit committee, the size of the company, the audit tenure, and reputation of KAP against going concern audit opinion. The object of this research is manufacturing companies listed in Indonesia Stock Exchange. Methods of sampling using purposive sampling techniques where appropriate criteria set acquired 21 companies. The data in this study were collected through non-participant observation method by downloading data from BEI. The analysis technique used is logistic regression analysis. Testing hypothesis in this study using logistic regression analysis techniques. Hypothesis testing results showed that the variables of the audit committee, company size, and audit tenure does not affect the going concern audit opinion, while the reputation of KAP variables significantly influence the going concern audit opinion.
Keywords: audit committee, size of the company, audit tenure, reputation of the firm, going concern audit opinion